The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000007495
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological evolution of remnant pancreas after resection for pancreatic adenocarcinoma

Abstract: Functional and morphological evolution of remnant pancreas after resection for pancreatic adenocarcinoma is investigated.The medical records of 45 patients who had undergone radical resection for pancreatic adenocarcinoma from March 2010 to September 2013 were reviewed retrospectively. There were 34 patients in the pancreaticoduodenectomy (PD) group and 10 patients in the distal pancreatectomy (DP) group. One patient received total pancreatectomy. The endocrine function was measured using the glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…In our study, some patients showed a paradoxical increase in insulin excretion even after pancreatectomy, which was found in patients only after PD. Park et al 26 function in this study, previous reports indicated that fatty infiltration in pancreatic parenchyma 27 or the obstruction of main pancreatic duct would influence endocrine pancreatic function, 26 and these investigations would be a help to develop the prediction tool of NODM. To further validate our findings, we need to prospectively accumulate data on the predictive ability from multiple centers, referring to whether preoperative data predict the development of NODM.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In our study, some patients showed a paradoxical increase in insulin excretion even after pancreatectomy, which was found in patients only after PD. Park et al 26 function in this study, previous reports indicated that fatty infiltration in pancreatic parenchyma 27 or the obstruction of main pancreatic duct would influence endocrine pancreatic function, 26 and these investigations would be a help to develop the prediction tool of NODM. To further validate our findings, we need to prospectively accumulate data on the predictive ability from multiple centers, referring to whether preoperative data predict the development of NODM.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, some patients showed a paradoxical increase in insulin excretion even after pancreatectomy, which was found in patients only after PD. Park et al 26 reported similar cases, and they assumed that obstructive pancreatitis due to periampullary PDAC exacerbated glucose tolerance by inhibiting insulin secretion, and pancreatectomy for the periampullary tumor sometimes recovered the function in the remnant pancreas by releasing obstruction. In summary, insulin excretion was directly dependent on the resected pancreatic volume in patients undergoing DP, whereas patients undergoing PD did not always correspond to the sole factor of resected pancreatic volume.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Park et al retrospectively reviewed 45 patients who had undergone radical resection for pancreatic adenocarcinoma: 34 patients underwent pancreaticoduodenectomy, 10 patients distal pancreatectomy, and one received total pancreatectomy. Even if no data about weight loss and malabsorption were reported in their analysis, they found that DM often improved after surgery: diabetes resolution occurred in 20-57% of patients after pancreaticoduodenectomy and in 13% of patients after distal pancreatectomy [65].…”
Section: Surgery (Pancreatectomy)mentioning
confidence: 94%
“…In a previous study, the remnant pancreatic volume was found to be a significant risk factor for DM, but this relationship was stronger in patients who underwent DP, rather than PD 16 . Another study showed that obstructive pancreatitis caused by periampullary PDAC exacerbates glucose intolerance by inhibiting insulin secretion and that treatment of the periampullary tumor by pancreatectomy sometimes permits the recovery of the function of the remnant pancreas by removing the obstruction 17 . However, the endocrine function of patients following PD cannot be explained by the remnant pancreas volume alone.…”
Section: Discussionmentioning
confidence: 94%